Imigrante, filantropo e confeiteiro : a vida de Nicolau Rocco (1856 – 1932) - Ambiedo, Fernanda Trentini (2023)
This thesis has as theme the italian urban imigration to Porto Alegre in the end of XIX and XX century. For that, we will investigate the life of the molisan immigrant Nicolau Rocco, that arrived in Porto Alegre in 1895 and with his capacity of interaction with nationals and italians radicated in the capital gaúcha has desenvolved his enterprise, the Confeitaria Rocco. So this thesis has as central problematic the understanding of his strategies as immigrant, philanthropist and baker in Porto Alegre and understand how he achieved a socially, culturally and politically active relevance during his lifetime. With this propose we going to analyses the molisano immigration to Brazil, the the associative organization of peninsular people in Porto Alegre, as well as their presence in associations such as Irmandade da Santa Casa de Misericórdia e Grande Oriente do Rio Grande do Sul and the operating structure of Confeitaria Rocco. As methodology we will use the precepts of microhistory, as the onomastic method and curated from several sources. The collections used range from newspaper libraries, oficial documents and family archives.